Rethinking Rape Laws Emphasizes the Central Role of Consent in Shaping Both Legal Frameworks and Public Understanding - Bergman, Stefano; Thunberg, Sophia (International Journal of Law and Public Policy (IJLAPP), 2025)
Sexual violence remains a significant concern worldwide, leading many countries to reassess their legal definitions of rape. Sweden's 2018 legal reform redefined rape based on the absence of consent rather than the presence of force, marking a significant shift in legal and societal perspectives. This study aims to evaluate the impact of this legislative change by analyzing conviction rates, public perception, and challenges faced by legal professionals. The research employs a mixed-methods approach, conducted throughout 2023, involving 500 respondents across Stockholm, Gothenburg, and Malmö. Data is collected through surveys, in-depth interviews with legal professionals, and court case analysis from three major district courts. Quantitative data is analyzed statistically to determine trends in conviction rates, while qualitative data undergoes thematic analysis. Findings reveal that conviction rates have increased from 15% in 2017 to 26% in 2023, indicating greater legal effectiveness. Public awareness surveys show 72% support for the consent-based definition, though concerns persist regarding the burden of proof and jury bias. Legal professionals highlight evidence challenges and victim reluctance to report cases, suggesting the need for further judicial training and legal support mechanisms. Future research should explore comparative analyses with other jurisdictions, assess long-term survivor experiences, and evaluate the effectiveness of legal education programs.